Pembangunan Masyarakat Berbasis Pengembangan Ekonomi Pesantren - Fitria Nurul Azizah; Musyafa Ali (Jurnal Ilmiah Ekonomi Islam, 2020)
This research focuses on the three main functions of boarding schools by revealing how Pondok Pesantren Rubat Mbalong Ell Firdaus conducts economic activities in pesantren and community development, and how islamic economic analysis related to community development based on economic development. This research is a type of field research through a qualitative descriptive approach. Data collection techniques use observation, interviews, and documentation. The results of the study illustrate that Pondok Pesantren Rubat Mbalong Ell Firdaus is a boarding school that implements economic activities and participates in community development by applying the educational format of tafaqquh and tadayyun. The concept of islamic education that is equipped with religious understanding while practising religious values, creating and applying the concept of Islam in view of the world. For the philosophical foundation of development in the Islamic perspective applied in Pondok Pesantren Rubat Mbalong Ell Firdaus namely tauheed uluhiyah, tauheed rububbiyah, khilafah, tazkiyyah an-nas and al-falah (optimizing human resources, applying god spot management, taking good care of nature, applying the Islamic mindset of rahmatallil religion and islam easy religion).